2020
DOI: 10.1101/2020.04.06.027771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Advanced Maternal Age on Physiologic Adaptations to Pregnancy in Vervet Monkeys

Abstract: 26Context: The trend to delay pregnancy in the United States has resulted in the number of 27 advanced maternal age (AMA) pregnancies to also increase. In humans, AMA is associ-28 ated with a variety of pregnancy-related pathologies such as preeclampsia (PE). While 29 AMA is known to be a factor which contributes to the development of pregnancy-induced 30 diseases, the molecular and cellular mechanisms giving rise to this phenomenon are still 31 very limited. This is due in part to lack of a pre-clinical model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…An inadequate diet and lack of natural food are associated with poor maternal conditions and high mortality rates of neonates (Fairbanks & McGuire, 1995;Hauser & Fairbanks, 1988). Vervets risk developing diabetes or being insulin resistant and hyperglycaemic, which may harm parturition (Kavanagh et al, 2011;Plant et al, 2020aPlant et al, , 2020b. Alternatively, increased anthropogenic food may result in increased foetal body masses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An inadequate diet and lack of natural food are associated with poor maternal conditions and high mortality rates of neonates (Fairbanks & McGuire, 1995;Hauser & Fairbanks, 1988). Vervets risk developing diabetes or being insulin resistant and hyperglycaemic, which may harm parturition (Kavanagh et al, 2011;Plant et al, 2020aPlant et al, , 2020b. Alternatively, increased anthropogenic food may result in increased foetal body masses.…”
Section: Discussionmentioning
confidence: 99%
“…Parturition in vervets is generally a solitary event at night while roosting in trees (Fairbanks & McGuire, 1984). Most studies on parturition in vervets have occurred in captive populations with access to veterinarian care (Fairbanks & McGuire, 1986; Kavanagh et al., 2011; Plant et al., 2020a, 2020b; Seier et al., 2000). This study describes novel evidence of birthing complications and dystocia observed in the parturition of wild vervets in the urban mosaic landscape of Durban, South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation